PERTUMBUHAN PASAR MODEREN DALAM MEREBUT KONSUMEN STUDI KASUS TOKO RITEL TRADISIONAL DI KOTA PEKANBARU - Saib, Khaidir (Sekolah Tinggi Ilmu Ekonomi Riau, 2018)
The rising growth of modern markets such as Hypermarket, Supermarke Departmen Store, and many more are creating considerable challenges for small and medium-sized retailers. In addition to large capitalization of funds, massive promotions through print and electronic media are able to attract the attention and interest of the community to visit their sales locations. compared to retailers who can only expect the loyalty of their customers only. This research is a case study using qualitative descriptive methodology. The research respondents are successful retail entrepreneurs in Pekanbaru city. The number of selected traditional retailers is 10 people, consisting of five retailers of nine basic commodities (sembako) and five clothing retailers. This study aims to find the jawapaban factor of sustainability of traditional retail business in Pekanbaru City. The findings of this research is one of the factors of traditional retail business in Pekanbaru City is a good communications pact retail business with customers, merchandise location factors and management factors swers to the commercial life of traditional retailers